Therapeutic Factors in Equine-Facilitated Group Psychotherapy for Women Survivors of Interpersonal Violence. Issue 4 (2nd October 2018) - Schroeder, Katy; Stroud, Daniel; Sherwood, Dawn M.; Udell, Monique A. R.
Abstract : This study entailed a qualitative content analysis of therapeutic factors in equine-facilitated group psychotherapy (EFGP) for women trauma survivors ( n = 9). Our findings indicated that instillation of hope, self-understanding, learning from interpersonal action, guidance, and acceptance frequently appeared in group members' narratives about their most important session events. These, as well as other group therapeutic factors, manifested in unique ways specific to the EFGP format. Clinical practice implications and new directions for future research investigations are discussed within the context of designing and delivering equine-facilitated therapy groups.